IMPLEMENTASI PENDIDIKAN MULTIKULTURAL MELALUI KEGIATAN SERIBU SABTU EMPATI DI SMA NEGERI 10 MATARAM - Hadijah, Hadjah; Irmi Ariani; Iziyandika , Iziyandika; Haerani, Janeva; Junaidi, Junaidi; Iziyandika , Sawaludin (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
This study aims to describe the implementation and impact of the Seribu Sabtu Empati program at SMAN 10 Mataram in shaping students’ social attitudes and multicultural behavior. This program is an experiential learning initiative that engages students in direct interaction with various community groups, including orphanages, the elderly, people with disabilities, and low-income families. A qualitative approach was employed to gain an in-depth understanding of students’ experiences through observation, interviews, questionnaires, and documentation. The findings show that the program successfully fosters empathy, reduces prejudice, enhances tolerance, and strengthens students’ inclusive behavior in daily interactions. However, the sustainability of these positive outcomes strongly depends on structured reflection, consistent program implementation, and a school culture that supports multicultural values. Therefore, Seribu Sabtu Empati serves not only as a social activity but also as an effective medium for cultivating caring, inclusive, and critically aware students